Sema3F (Semaphorin 3F) Selectively Drives an Extraembryonic Proangiogenic Program - Regano, Donatella (Arterioscler Thromb Vasc Biol, 2017)
OBJECTIVE—: Molecular pathways governing blood vessel patterning are vital to vertebrate development. Because of their ability to counteract proangiogenic factors, antiangiogenic secreted Sema3 (class 3 semaphorins) control embryonic vascular morphogenesis. However, if and how Sema3 may play a role in the control of extraembryonic vascular development is presently unknown. APPROACH AND RESULTS—: By characterizing genetically modified mice, here, we show that surprisingly Sema3F acts instead as a selective extraembryonic, but not intraembryonic proangiogenic cue. Both in vivo and in vitro, in visceral yolk sac epithelial cells, Sema3F signals to inhibit the phosphorylation-dependent degradation of Myc, a transcription factor that drives the expression of proangiogenic genes, such as the microRNA cluster 17/92. In Sema3f-null yolk sacs, the transcription of Myc-regulated microRNA 17/92 cluster members is impaired, and the synthesis of Myc and microRNA 17/92 foremost antiangiogenic target Thbs1 (thrombospondin 1) is increased, whereas Vegf (vascular endothelial growth factor) signaling is inhibited in yolk sac endothelial cells. Consistently, exogenous recombinant Sema3F inhibits the phosphorylation-dependent degradation of Myc and the synthesis of Thbs1 in mouse F9 teratocarcinoma stem cells that were in vitro differentiated in visceral yolk sac epithelial cells. Sema3f(−/−) mice placentas are also highly anemic and abnormally vascularized. CONCLUSIONS—: Sema3F functions as an unconventional Sema3 that promotes extraembryonic angiogenesis by inhibiting the Myc-regulated synthesis of Thbs1 in visceral yolk sac epithelial cells.